Chronic high‐caloric diet modifies sleep homeostasis in mice. (30th May 2018) - Panagiotou, Maria; Meijer, Johanna H.; Deboer, Tom
Abstract: Obesity prevalence and sleep habit changes are commonplace nowadays, due to modern lifestyle. A bidirectional relationship likely exists between sleep quality and metabolic disruptions, which could impact quality of life. In our study, we investigated the effects of a chronic high‐caloric diet on sleep architecture and sleep regulation in mice. We studied the effect of 3 months high‐caloric diet (HCD, 45% fat) on sleep and the sleep electroencephalogram (EEG) in C57BL/6J mice during 24‐hr baseline (BL) recordings, and after 6‐hr sleep deprivation (SD). We examined the effect of HCD on sleep homeostasis, by performing parameter estimation analysis and simulations of the sleep homeostatic Process S, a measure of sleep pressure, which is reflected in the non‐rapid‐eye‐movement (NREM) sleep slow‐wave‐activity (SWA, EEG power density between 0.5 and 4.0 Hz). Compared to controls ( n = 11, 30.7 ± 0.8 g), mice fed with HCD ( n = 9, 47.6 ± 0.8 g) showed an increased likelihood of consecutive NREM‐REM sleep cycles, increased REM sleep and decreased NREM sleep EEG SWA. After SD, these effects were more pronounced. The simulation resulted in a close fit between the time course of SWA and Process S in both groups. HCD fed mice had a slower time constant ( T i = 15.98 hr) for the increase in homeostatic sleep pressure compared with controls (5.95 hr) indicating a reduced effect of waking on the increase in sleep pressure. Our results suggest that chronic HCD consumption impacts sleep regulation. Abstract : Obesity has been associated with sleep disorders that could impact quality of life. We investigated the effect of high‐caloric‐diet‐induced obesity in mice on sleep architecture and sleep regulation. A NREM sleep episode was more likely to be followed by a REM sleep episode and less likely to be followed by a waking episode in high‐caloric diet‐treated mice. In addition, a slower build‐up of sleep pressure and decreased slow‐wave‐activity in NREM sleep was induced following high‐caloric diet, leading to an altered sleep homeostasis.